Screen-printable films of graphene/CoS2/Ni3S4 composites for the fabrication of flexible and arbitrary-shaped all-solid-state hybrid supercapacitors - Jiang, Degang; Liang, Hui; Yang, Wenrong; Liu, Yan; Cao, Xueying; Zhang, Jingmin; Li, Chenwei; Liu, Jingquan; Gooding, J. Justin (Carbon (New York), 2019)
Supercapacitors are attracting increasing research interest because they are expected to achieve battery-level energy density while having a long calendar life and a short charging time. However, the development of large-scale and cost-reasonable production methods for flexible, wearable and arbitrary-shaped supercapacitor devices still faces enormous challenges. Herein, a 3D-network, porous graphene/CoS2/Ni3S4 (G/CoS2/Ni3S4) composite electrode has been designed and synthesized through a combination of solvothermal and vulcanization methods. By combining the networked CoS2/Ni3S4 nanoflakes with reduced graphene oxide (RGO) nanosheets, the as-prepared composite electrode exhibits good conductivity, a high density of electrochemically active sites and good cycling stability. The result is a high specific capacitance of 1739 F g−1 at a current density of 0.5 A g−1. Significantly, the arbitrary-shaped G/CoS2/Ni3S4||GF hybrid supercapacitor devices can be printed directly on different substrates, which favorably combine mechanical flexibility, good cycling performance and high energy density. This methodology may be feasible to prepare fully-printable and wearable supercapacitors, and other electronic devices in large scale, thereby holding enormous potential for wearable technologies. [Display omitted]